Anti–PD-L1 Therapy Does Not Improve Survival in a Murine Model of Lethal Staphylococcus aureus Pneumonia. (19th May 2021) - Curran, Colleen S; Busch, Lindsay M; Li, Yan; Xizhong, Cui; Sun, Junfeng; Eichacker, Peter Q; Torabi-Parizi, Parizad
Abstract: Background: Staphylococcus aureus ( SA ) bacterial pneumonia is a common cause of sepsis in intensive care units. Immune checkpoint inhibitors (CPIs) that target programmed cell death protein 1 (PD-1) and its ligand (PD-L1) have been proposed for the treatment of sepsis. However, in our systematic review of sepsis preclinical models, none of the models examined CPIs in pneumonia. Methods: Mice were inoculated intratracheally with vehicle control, low dose (LD)- or high dose (HD)- SA . Immune cell recruitment and checkpoint molecule expression were examined at 4, 24, and 48 hours after infection. Infected animals, treated with control or anti–PD-L1 antibodies, were assessed for survival, bacterial burden, lung immunophenotypes, and mediator production. Results: LD- SA and HD- SA produced lethality of 15% and 70%, respectively, by 168 hours. At 24 hours, LD-infected animals exhibited increased lung monocyte PD-L1 expression ( P = .0002) but lower bacterial counts ( P = .0002) compared with HD animals. By 48 hours, either infection induced lung neutrophil and macrophage PD-L1 expression ( P < .0001). Anti–PD-L1 treatment at the time of infection and at 24 hours following infection with low to high doses of SA reduced PD-L1 detection but did not affect survival or bacterial clearance. Conclusions: Anti–PD-L1 therapy did not alter survival in this pneumonia model. Preclinical studies of additional common pathogens and septic foci are needed. Abstract : Despite increased expression of immune-cell programmed death 1 protein and its ligand (PD-L1) in a pneumonia model, PD-L1 inhibition did not improve survival. The time of antibody administration, dosing regimen, type of microbe, or the site of infection may affect the response.